Passively Q-switched S+/S band fiber laser with copper telluride saturable absorber. (29th July 2020) - Ahmad, H; Azmy, N F; Kasran, F a M; Yusoff, N; Reduan, S A; Bayang, L; Ismail, M F; Zulkifli, M Z; Thambiratnam, K
Abstract: A Q-switched S-band fiber laser based on a thulium-fluoride fiber gain medium and copper telluride (Cu2 Te) based saturable absorber (SA) is demonstrated. The Cu2 Te based SA is fabricated as a thin film and at the maximum pump power, the generated Q-switched output has a minimum pulse width of 3.2 µ s and highest pulse energy of 56.7 nJ. The pulse train varies from 20.9 kHz to 30.2 kHz at the highest pump power. The wavelength of the generated output can be tuned over a range of 32 nm from 1470 nm to 1502 nm. The demonstrated laser has a high potential for industrial applications focusing on the S-band region.